Inkonsistensi UU Nomor 4 Tahun 2009 Tentang Minerba Khususnya Dalam Hal Pemberdayaan Hak Mayarakat Hukum Adat - Panggabean, H. P. (LAW REVIEW, 2011)
The indigenous rights of the Mahudat people should be a primary consideration in establishing an equitable mining regime in Indonesia. The new mining law has devolved significant authority to local governments that must warrant or assure the tenure and ownership of indigenous peoples to their lands and the mineral resources found therein. The District Governments need to develop new instruments and modalities to balance competing interests between economic development and social and environmental well-being primarily by requiring mining companies to negotiate with these indigenous people to find new formulations for cooperative and equitable partnerships, which include among others: identification of land in customary areas that can or should not be mined (either because of cultural considerations/religious or ecology); rehabilitation of environmental damage; reparation for harm on indigenous inhabitants of the mining areas; and equitable sharing of benefits of mining production.